Implementasi Kebijakan Pogram Pemberdayaan Masyarakat Dalam Mewujudkan Kota Tanpa Kumuh ( KOTAKU ) Kabupaten Wonosobo 2020 - suharto suharto (LP2M, 2022)
The community empowerment program is by paying attention to all aspects of community life with the aim of all levels of society being self-reliant (independent), so as to generate self-help abilities. to improve people's quality of life (modernization) which refers to the way of thinking, behaving, behaving. The implementation of the Tridaya approach in the slum-free city program (KOTAKU) includes: (1) empowerment of local governments and communities through capacity building in the form of training and mentoring; (2) utilization of environmental facilities by improving the quality of the residential environment through the procurement and improvement of primary basic infrastructure and facilities as well as repairing unfit houses; and (3) community economic empowerment carried out through channeling with other programs in the field of Public Works and various activities carried out in the regions. To get a comprehensive picture of the program, researchers need to evaluate the policy of the KOTAKU (City without Slums) Kab. Wonosobo in 2020.It can be said that by knowing the implementation of community empowerment program policies in realizing KOTAKU (City Without Slums) Wonosobo Regency in 2020, pro-poor programs (pro-poor) can be measured and controlled to achieve an empowered, independent and civil society in the future. which will come according to the vision and mission of Wonosobo Regency.